Proteomic Discovery of Diabetic Nephropathy Biomarkers - Merchant, Michael L. (2010)
Diabetes mellitus (DM) is a complex systemic disease, with complications that result from both genetic predisposition and dysregulated metabolic pathways. DM is a highly prevalent disease with current estimates that there are 17.5 million diagnosed and 6.6 million un-diagnosed diabetics in the United States. DM and its complications impose a significant societal and economic burden. The medical costs of the most common microvascular complications of uncontrolled DM, diabetic nephropathy (DN) and diabetic retinopathy, account for 29% and 15% respectively of the $116 billion expenditures associated with diabetes. A substantial gap in our knowledge exists of the understanding these complications. In order to advance therapy and decrease the societal burden of DM there is a clear need for biomarkers that can diagnose DN early and predict its course. Proteomics has evolved into a high-throughput, analytical discipline used to analyze complex biological datasets. These open-ended, hypothesis generating approaches, when appropriately designed and interpreted, are well suited to the study of the pathogenic mechanisms of diabetic microvascular disease and the identification of biomarkers of DN. We will review here the evolving role that proteomics has played in expandingour understanding of the diagnosis and pathogenesis of DN.